Mobility as a function of environmental conditions and sociodemographic differentiation: the case of gender inequality in the Lisbon Metropolitan Area - Carmo, R. M. (2020)
Place determinants and social dimensions interact to produce mobility patterns. The article seeks to measure to what extent the physical and social conditions of the residency place modulate the intensity of mobility particularly in what concerns gender inequalities. To do so, we first present the theoretical framework, which guides our perspective on mobility inequalities and the geographical focus: Lisbon Metropolitan Area (LMA). Secondly, using logistic regression on representative data from a survey to LMA inhabitants we elaborate on the concept of environmental motility and its relationship to various types of inequality. Lastly, we systematize a view on accumulated inequalities examining how local environments may increase the mobilities gender gap.